Bridging electrocatalyst and cocatalyst studies for solar hydrogen production via water splitting. Issue 10 (8th February 2022) - Saruyama, Masaki; Pelicano, Christian Mark; Teranishi, Toshiharu
Abstract : This perspective briefly reviews recently developed water splitting electrocatalyst materials and discusses their utilization as cocatalysts for photocatalytic and photoelectrochemical water splitting systems. Abstract : Solar-driven water-splitting has been considered as a promising technology for large-scale generation of sustainable energy for succeeding generations. Recent intensive efforts have led to the discovery of advanced multi-element-compound water-splitting electrocatalysts with very small overpotentials in anticipation of their application to solar cell-assisted water electrolysis. Although photocatalytic and photoelectrochemical water-splitting systems are more attractive approaches for scaling up without much technical complexity and high investment costs, improving their efficiencies remains a huge challenge. Hybridizing photocatalysts or photoelectrodes with cocatalysts has been an effective scheme to enhance their overall solar energy conversion efficiencies. However, direct integration of highly-active electrocatalysts as cocatalysts introduces critical factors that require careful consideration. These additional requirements limit the design principle for cocatalysts compared with electrocatalysts, decelerating development of cocatalyst materials. This perspective first summarizes the recent advances in electrocatalyst materials and the effective strategies to assemble cocatalyst/photoactive semiconductor composites, and further discusses the core principles and tools that hold the key in designing advanced cocatalysts and generating a deeper understanding on how to further push the limits of water-splitting efficiency.